Valuing digital possessions: the role of affordances. Issue 6 (14th October 2022) - Denegri-Knott, Janice; Jenkins, Rebecca; Lindley, Siân
Abstract: In this article, we introduce an affordance-orientated approach for the study of digital possessions. We identify affordances as a source of value for digital possessions and argue that dominant meaning-orientated approaches do not enable us to fully appreciate these sources of value. Our work recognizes that value is released and experienced in "the doing"—people must do things with digital objects to locate and obtain value in and from them. We distinguish three levels of affordance for digital possessions—low, mid, and high—and introduce the concept of digital incorporation to explain how the three levels of affordances come together, with the individual's own intentionality to enable the achievement of goals. We draw from postphenomenological interviews with 47 individuals in the UK to provide a possession-based and lived experience approach to affordances that sheds new light on their vital role in everyday life and goals.